Petrogenesis of the Natkusiak continental basalts, Victoria Island, Northwest Territories, Canada - Dostal, J.; Baragar, W. R. A.; Dupuy, C. (Canadian Journal of Earth Sciences, 1986)
The Natkusiak flows (~1100 m thick), sills, and dykes of Victoria Island, Northwest Territories, are part of an extensive, late Hadrynian magmatic event in the northern Canadian Shield. The flows are subaerially erupted plateau basalts and together with associated doleritic sills and dykes display many geochemical features typical of continental tholeiites. In addition to fractional crystallization, the rocks were affected by crustal contamination but to a smaller degree than usually encountered in continental tholeiites elsewhere. The basalts were derived from a depleted upper mantle source very similar to that of N-type mid-ocean ridge basalts, although it is suggested that the melting residue contained small amounts of garnet (~2%).